A Study of Mobile Payments: Understanding the Determinants of Consumer Adoption - Mmbwanga, Brenda (2011)
Advances in technology have resulted in innovative and efficient ways of making payments, one example being the emergence of electronic-based payment systems which are now possible through mobile devices such as mobile phones. Reports by various researchers show that the number of mobile phone subscriptions worldwide continues to grow rapidly. A surprising fact, however, is that there is a relatively low rate of adoption of mobile payments by consumers in Malaysia. This research attempts to understand the factors that influence consumers to make use of mobile payment services. The Theory of Reasoned Action is applied (TRA) and an investigation is carried out, testing the proposed hypotheses and model. SPSS 17 is used for analysis, where factor analysis, oneway ANOVA, Kruskal Wallis test, correlation, and regression methods are employed. Results show that consumer subjective norms and attitudes they have towards mobile payments both influence their intention to use mobile payments, subsequently influencing their decision to adopt mobile payments. The findings contribute to the understanding of mobile payments for the relevant industry players.